Eco-Edutainment Model on Water Environment Pollution Case for Social Science Learning Junior High School in Semarang - Apik Budi Santoso, Dewi Liesnoor Setyowati, Wasino, Purwadi Suhandini (International Journal of Advanced Science and Technology, 2020)
The influence of the 4.0 industrial revolution has now penetrated all aspects of life. Education has become one aspect of the social life of people who inevitably are affected by the development of industry 4.0. Thus learning with a "traditional" curriculum tends to be irrelevant with the times. Fun and environmentally friendly eco-edutainment is a model that was developed in this research by harmonizing the concept of joyful learning. This learning model can be said to be relevant to industry development 4.0. The purpose of this study was to determine the effectiveness of the eco-edutainment model in social science learning in aspects of the water environment. The target of this research was SMP Negeri 14 Semarang, and SMP Negeri 28 Semarang, both of which indeed exist in low-land areas with the complexity of water environment conditions. The results obtained that the application of the model in this study showed high effectiveness seen from four main indicators, including teacher response, student activity, student response, and student learning outcomes.